A global meta‐analysis of temperature effects on marine fishes' digestion across trophic groups. Issue 4 (31st January 2021) - Knight, Nicole S.; Guichard, Frédéric; Altieri, Andrew H.
Abstract: Aim: The temperature constraint hypothesis proposes that marine herbivorous fishes are rare at high latitudes relative to carnivorous fishes because low temperatures impair the digestion of plant material. To test this hypothesis, we compared the effects of temperature on the digestive performance and investment in digestion of marine fishes across trophic groups. Location: Global marine ecosystems. Major taxa studied: Marine fishes. Methods: We analysed data from 304 species consuming a range of diets to quantify the effects of temperature on three indicators of digestive performance and investment: gut passage time, absorption efficiency, and gut length. Results: Decreasing temperatures increase gut passage time in fishes consuming macroalgae more than fishes consuming other fish or invertebrates. Low temperatures do not impair absorption efficiency in fishes regardless of diet, but herbivores have lower absorption efficiencies than carnivores overall. Gut length decreases with decreasing temperature in all trophic groups. Main conclusions: Our analyses reveal limited evidence to support the temperature constraint hypothesis. Low temperatures slow digestion more in fishes consuming macroalgae than those consuming animal prey; however, this may not reflect a meaningful disadvantage for herbivores but rather could be explained by greater representation of fishes relying on microbial fermentation at high latitudes. Herbivorous fishes absorb nutrients and energy from their food in similar proportions regardless of temperature, in contrast to the expectations of the temperature constraint hypothesis. Decreased gut length was associated with decreasing temperature across all trophic groups, likely due to improved food quality at high latitudes, which should benefit all trophic groups by reducing their required investment in gut tissues. Altogether, our findings run counter to the general hypothesis that low temperatures disadvantage the digestion of plant material and suppress the diversity and abundance of herbivorous fishes at high latitudes.